Inoculation of Cilantro (Coriandrum sativum L.) with Rhizobacterias in Villa del Rosario, Norte de Santander (2015)
Plant growth promoting rhizobacteria (PGPR) represent an alternative biofertilization form. In this study, was evaluated PGPR inoculation in cilantro plants. Likewise, was evaluated the practice of burning rice husk in soil preparation for crop establishment. An experimental design was used in a split plot where the main plots were soil preparation with burning rice husk and without burning rice husk with prior inoculation of Trichoderma sp. The subplots correspond to treatments with simple inoculation and co-inoculation of Azotobacter RzH120 and Azospirillum RzH132 and chemical and absolute control. Once the assumptions were tested in model residuals, normality, homogeneity of variance and randomness, an analysis of variance and multiple comparison tests by Tukey's test and principal component analysis technique was performed as size reduction. According to principal component analysis, the results showed a positive effect on the growth of plants inoculated with PGPR in the two plots with burning and without burning rice husk, however, the variable yield (P≤0.05). Also, it was found that the population of bacteria in the rhizosphere culture media NFb semisolid, Ashby and King B, was not favored by the burning of rice husks on the soil. Importantly, the results were obtained with the 30% decrease in the chemical fertilizer, which can reduce the use of these chemicals.